Promoting Education 4.0 in English for Survival Class: What are the Challenges? - Candradewi Wahyu Anggraeni (Metathesis: Journal of English Language, Literature, and Teaching, 2018)
Abstract Education 4.0 is a new paradigm in educational context in which it focuses on the innovation and maximizes the use of information, internet, and technology. This new paradigm is currently promoted in many subjects, including English subjects in English Education Study Program of Universitas Tidar. One of the subjects that promote Education 4.0 is English for Survival. Therefore, this study reports to explore the challenges in promoting Education 4.0 in English for Survival classes. This study uses qualitative research in the form of case study. The participants of this study are the lecturers and the students of English for Survival classes. The instruments of data collection are questionnaire and interview. The finding shows that three challenges revealed in promoting Education 4.0 in which they cover lecturer’s teaching technique, students’ speaking skill, and facilities. Besides, the lecturers and the students need to highlight those challenges and solve those problems. All in all, against all the odds of promoting Education 4.0, the lecturers and students need to apply Education 4.0 in order to help the students to compete in the era of 4.0. Keywords: Education 4.0, speaking, autonomous learning, perceptions